Remote Sensing Through Millimeter Wave Radiometer Sensor - Kumar, Ashok; Jassal, B. S. (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*304.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.939222);" role="presentation">The extension of imaging techniques from shorter wave length of IR and <span dir="ltr" style="left: calc(var(–scale-factor)*374.23px); top: calc(var(–scale-factor)*304.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.967469);" role="presentation">visible to <span dir="ltr" style="left: calc(var(–scale-factor)*415.03px); top: calc(var(–scale-factor)*304.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.949461);" role="presentation">longer wave length of mm <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*317.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.940004);" role="presentation">wave invites <span dir="ltr" style="left: calc(var(–scale-factor)*126.38px); top: calc(var(–scale-factor)*317.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.914229);" role="presentation">substantial penalties to <span dir="ltr" style="left: calc(var(–scale-factor)*222.53px); top: calc(var(–scale-factor)*317.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.943796);" role="presentation">be paid in terms of size and spatial resolution. In spite of the above cited <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*330.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.951025);" role="presentation">limitations, passive imaging senso<span dir="ltr" style="left: calc(var(–scale-factor)*215.45px); top: calc(var(–scale-factor)*330.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.972115);" role="presentation">rs have gained popularity due to its superior performance under <span dir="ltr" style="left: calc(var(–scale-factor)*492.82px); top: calc(var(–scale-factor)*330.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.859134);" role="presentation">adverse <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*343.73px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.888362);" role="presentation">weather <span dir="ltr" style="left: calc(var(–scale-factor)*107.66px); top: calc(var(–scale-factor)*343.73px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.957823);" role="presentation">conditions i.e. fog, dust &battle field smoke. Besides operating under stealth conditions the images <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*356.93px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.937885);" role="presentation">generated have a high contrast, stable signature and provide easy <span dir="ltr" style="left: calc(var(–scale-factor)*349.99px); top: calc(var(–scale-factor)*356.93px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.927602);" role="presentation">interpret<span dir="ltr" style="left: calc(var(–scale-factor)*383.95px); top: calc(var(–scale-factor)*356.93px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.992647);" role="presentation">ation of <span dir="ltr" style="left: calc(var(–scale-factor)*420.43px); top: calc(var(–scale-factor)*356.93px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.883208);" role="presentation">images. <span dir="ltr" style="left: calc(var(–scale-factor)*455.38px); top: calc(var(–scale-factor)*356.93px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.990485);" role="presentation">Millimeter wave <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*370.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00187);" role="presentation">imaging through passive radiometric sensor is proving to be a great boon for <span dir="ltr" style="left: calc(var(–scale-factor)*414.31px); top: calc(var(–scale-factor)*370.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.965039);" role="presentation">the covert <span dir="ltr" style="left: calc(var(–scale-factor)*461.74px); top: calc(var(–scale-factor)*370.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.967373);" role="presentation">surveillance of <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*383.33px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.959939);" role="presentation">battlefield by sensing the <span dir="ltr" style="left: calc(var(–scale-factor)*181.70px); top: calc(var(–scale-factor)*383.33px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.873917);" role="presentation">manmade <span dir="ltr" style="left: calc(var(–scale-factor)*224.69px); top: calc(var(–scale-factor)*383.33px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.963068);" role="presentation">objects, and armored vehicles from a remote platform. The <span dir="ltr" style="left: calc(var(–scale-factor)*478.30px); top: calc(var(–scale-factor)*383.33px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.012);" role="presentation">all-<span dir="ltr" style="left: calc(var(–scale-factor)*491.74px); top: calc(var(–scale-factor)*383.33px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.888643);" role="presentation">weather <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*396.55px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.956236);" role="presentation">capability of <span dir="ltr" style="left: calc(var(–scale-factor)*125.18px); top: calc(var(–scale-factor)*396.55px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.9285);" role="presentation">mm wave imaging <span dir="ltr" style="left: calc(var(–scale-factor)*202.49px); top: calc(var(–scale-factor)*396.55px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.889913);" role="presentation">sensor provides <span dir="ltr" style="left: calc(var(–scale-factor)*267.77px); top: calc(var(–scale-factor)*396.55px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.889762);" role="presentation">the necessary edge over the other technologies as part of sensor <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*409.87px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.922746);" role="presentation">suit <span dir="ltr" style="left: calc(var(–scale-factor)*90.62px); top: calc(var(–scale-factor)*409.87px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.996);" role="presentation">for <span dir="ltr" style="left: calc(var(–scale-factor)*106.46px); top: calc(var(–scale-factor)*409.87px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.932245);" role="presentation">imaging. <span dir="ltr" style="left: calc(var(–scale-factor)*145.82px); top: calc(var(–scale-factor)*409.87px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.957286);" role="presentation">Passive mm wave imaging system develops a picture by det<span dir="ltr" style="left: calc(var(–scale-factor)*400.51px); top: calc(var(–scale-factor)*409.87px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.945734);" role="presentation">ecting non-<span dir="ltr" style="left: calc(var(–scale-factor)*447.34px); top: calc(var(–scale-factor)*409.87px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.911717);" role="presentation">coherent noise <span dir="ltr" style="left: calc(var(–scale-factor)*511.18px); top: calc(var(–scale-factor)*409.87px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.918059);" role="presentation">i.e. <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*423.07px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.901999);" role="presentation">Radiant <span dir="ltr" style="left: calc(var(–scale-factor)*106.70px); top: calc(var(–scale-factor)*423.07px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.945409);" role="presentation">electromagnetic energy. In this band, emissivi<span dir="ltr" style="left: calc(var(–scale-factor)*296.81px); top: calc(var(–scale-factor)*423.07px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.968592);" role="presentation">ty varies greatly from near zero for metallic objects to <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*436.27px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.942386);" role="presentation">nearly one for natural objects like vegetation. Metallic objects appear very cold <span dir="ltr" style="left: calc(var(–scale-factor)*400.87px); top: calc(var(–scale-factor)*436.27px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.928881);" role="presentation">to a <span dir="ltr" style="left: calc(var(–scale-factor)*419.59px); top: calc(var(–scale-factor)*436.27px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.946894);" role="presentation">passive MM <span dir="ltr" style="left: calc(var(–scale-factor)*473.50px); top: calc(var(–scale-factor)*436.27px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.889311);" role="presentation">wave sensor <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*449.47px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.937391);" role="presentation">due to <span dir="ltr" style="left: calc(var(–scale-factor)*101.90px); top: calc(var(–scale-factor)*449.47px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00513);" role="presentation">their low <span dir="ltr" style="left: calc(var(–scale-factor)*142.94px); top: calc(var(–scale-factor)*449.47px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.977436);" role="presentation">emissivity (high reflectivity) relative to terrain and other non-<span dir="ltr" style="left: calc(var(–scale-factor)*400.51px); top: calc(var(–scale-factor)*449.47px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.963123);" role="presentation">metalli<span dir="ltr" style="left: calc(var(–scale-factor)*428.23px); top: calc(var(–scale-factor)*449.47px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.95862);" role="presentation">c objects in the image. <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*462.67px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.966063);" role="presentation">Because, these metallic objects are almost totally reflective, so any type of counter measure will have little <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*475.99px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.963739);" role="presentation">effect on their detection. The key to passive MM wave imaging is the large temperature contrast in the MM <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*489.19px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.920735);" role="presentation">wave spectral b<span dir="ltr" style="left: calc(var(–scale-factor)*135.86px); top: calc(var(–scale-factor)*489.19px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.948697);" role="presentation">and due to large variation in emissivity value for the various target materials a<span dir="ltr" style="left: calc(var(–scale-factor)*459.94px); top: calc(var(–scale-factor)*489.19px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.954488);" role="presentation">nd terrain in an <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*502.39px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.887622);" role="presentation">imaged scene. <span dir="ltr" style="left: calc(var(–scale-factor)*133.10px); top: calc(var(–scale-factor)*502.39px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.912837);" role="presentation">Temperature <span dir="ltr" style="left: calc(var(–scale-factor)*187.73px); top: calc(var(–scale-factor)*502.39px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.936057);" role="presentation">contrast of greater than 100 times the contrast of IR systems are commo<span dir="ltr" style="left: calc(var(–scale-factor)*487.42px); top: calc(var(–scale-factor)*502.39px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.979109);" role="presentation">n for the <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*515.59px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.911401);" role="presentation">systems operating in <span dir="ltr" style="left: calc(var(–scale-factor)*158.42px); top: calc(var(–scale-factor)*515.59px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.981348);" role="presentation">the MM wav<span dir="ltr" style="left: calc(var(–scale-factor)*211.13px); top: calc(var(–scale-factor)*515.59px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.892315);" role="presentation">e spectral band as a<span dir="ltr" style="left: calc(var(–scale-factor)*291.29px); top: calc(var(–scale-factor)*515.59px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.937532);" role="presentation">ny material <span dir="ltr" style="left: calc(var(–scale-factor)*340.15px); top: calc(var(–scale-factor)*515.59px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.886332);" role="presentation">at a <span dir="ltr" style="left: calc(var(–scale-factor)*358.03px); top: calc(var(–scale-factor)*515.59px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.896679);" role="presentation">temperature above absolute zero <span dir="ltr" style="left: calc(var(–scale-factor)*492.46px); top: calc(var(–scale-factor)*515.59px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.87684);" role="presentation">radiates <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*528.79px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.987575);" role="presentation">in microwave, Millimeter wa<span dir="ltr" style="left: calc(var(–scale-factor)*192.53px); top: calc(var(–scale-factor)*528.79px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.888046);" role="presentation">ve <span dir="ltr" style="left: calc(var(–scale-factor)*205.73px); top: calc(var(–scale-factor)*528.79px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.925665);" role="presentation">and other spectral regions. <span dir="ltr" style="left: calc(var(–scale-factor)*319.03px); top: calc(var(–scale-factor)*528.79px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.965677);" role="presentation">All objects in a given scene of interest are either <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*542.11px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.946287);" role="presentation">reflecting or radiating electromagnetic energy <span dir="ltr" style="left: calc(var(–scale-factor)*264.65px); top: calc(var(–scale-factor)*542.11px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.955418);" role="presentation">in a given spectral band. <span dir="ltr" style="left: calc(var(–scale-factor)*371.83px); top: calc(var(–scale-factor)*542.11px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.90889);" role="presentation">Present paper d<span dir="ltr" style="left: calc(var(–scale-factor)*436.27px); top: calc(var(–scale-factor)*542.11px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.883374);" role="presentation">iscusses the usage <span dir="ltr" style="left: calc(var(–scale-factor)*515.14px); top: calc(var(–scale-factor)*542.11px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00439);" role="presentation">of <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*555.31px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.904332);" role="presentation">94<span dir="ltr" style="left: calc(var(–scale-factor)*82.10px); top: calc(var(–scale-factor)*555.31px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.942541);" role="presentation">GHz imaging <span dir="ltr" style="left: calc(var(–scale-factor)*139.22px); top: calc(var(–scale-factor)*555.31px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.904244);" role="presentation">sensors with <span dir="ltr" style="left: calc(var(–scale-factor)*192.29px); top: calc(var(–scale-factor)*555.31px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.929987);" role="presentation">single receiving <span dir="ltr" style="left: calc(var(–scale-factor)*259.01px); top: calc(var(–scale-factor)*555.31px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.914508);" role="presentation">elements for the purpose of surveillance, <span dir="ltr" style="left: calc(var(–scale-factor)*426.19px); top: calc(var(–scale-factor)*555.31px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.921056);" role="presentation">its detection <span dir="ltr" style="left: calc(var(–scale-factor)*478.06px); top: calc(var(–scale-factor)*555.31px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.923023);" role="presentation">capabilities <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*568.54px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.886166);" role="presentation">and image <span dir="ltr" style="left: calc(var(–scale-factor)*115.82px); top: calc(var(–scale-factor)*568.54px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.919055);" role="presentation">data of the metallic <span dir="ltr" style="left: calc(var(–scale-factor)*195.41px); top: calc(var(–scale-factor)*568.54px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.899997);" role="presentation">targets in <span dir="ltr" style="left: calc(var(–scale-factor)*234.77px); top: calc(var(–scale-factor)*568.54px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.897233);" role="presentation">the background of ocean, <span dir="ltr" style="left: calc(var(–scale-factor)*338.35px); top: calc(var(–scale-factor)*568.54px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.945292);" role="presentation">land and hilly <span dir="ltr" style="left: calc(var(–scale-factor)*395.83px); top: calc(var(–scale-factor)*568.54px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.919236);" role="presentation">terrain